ONLINE DISPUTE RESOLUTION: A MODERN ART OF ADJUDICATION - Mishra, Ashutosh; Kharat, Madhuri; Sonawane, Ajay; Shukla, Shruti; Maurya, Suraj Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Online dispute resolution is basically a technique where disputes of the physical world and disputes of cyberspace can be solved in a better way, whether the dispute resolution procedure is completely online or partly online. But here the first question is; what are the areas where online dispute resolution processes may be helpful to solve disputes? And the second question is whether it is suitable to a particular environment? Basically, it is mooted by various jurists that e-commerce is the suitable place where online dispute resolution can help to provide justice to the community. But this is not a complete statement and the importance of online dispute resolution processes is much more than this fact. Number of other areas have been identified by various writers and practice in different countries shows the use of ODR in different fields. Online dispute resolution, similarly as ADR, is a range of processes and forms. ODR emphasized on how to do, rather than what to do? In future, most dispute resolution processes will likely migrate to online processes, and ODR will be useful to almost every type of dispute.